Key Regional Commodities for Social Forestry Development in Penyabungan, Mandailing Natal Regency, North Sumatra - Syaiful, Syufriandi; Bahruni; Trison, Soni; Darusman, Dudung (Jurnal Sylva Lestari, 2025)
Social forestry is a government initiative program that promotes sustainable forest management to enhance community welfare. Mandailing Natal Regency is rich in timber and non-timber forest products (NTFP). This study aims to analyze key and non-key NTFP commodities, changes in growth patterns, and shifts within the biopharmaceutical and fruit sectors relevant to the concept of multiple-use forestry (MUF) under the framework of social forestry in Forest Management Unit IX Penyabungan, Mandailing Natal Regency. Location Quotient (LQ) and Shift-Share (SS) analysis were combined to map and identify local commodities that could become key commodities for social forestry development in Penyabungan, Mandailing Natal Regency, North Sumatra. The results indicated that cinnamon, cocoa, sugar palm, and candlenuts are the essential NTFP commodities with  LQ value > 1. Meanwhile, galangal, turmeric, laos, wild ginger, and curcuma dominate the biopharmaceutical products with  LQ value > 1. Among fruits, starfruit, langsat, durian, guava, jengkol, mango, mangosteen, melinjo, jackfruit, petai, rambutan, and breadfruit are identified as essential commodities with LQ value > 1. While the MUF sectors related to forestry and fruit show positive growth trends, the biopharmaceutical sector exhibits a negative shift. This study suggests that agroforestry development in the social forest at Mandailing Natal could benefit the biopharmaceutical sector, creating job opportunities and increasing farmers’ incomes. Keywords: agroforestry, community economy, location quotient, multi-use forestry, shift-share analysis